2019
DOI: 10.1055/a-0977-5478
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric-concentric Ratio: A Key Factor for Defining Strength Training in Soccer

Abstract: The aims of this study were to analyse the effect of chronic strength training over concentric power (CON), eccentric power (ECC), ECC/CON ratio, and 20 m linear sprint performance in elite young soccer players. Twenty young elite Spanish soccer players were assigned to an experimental group (CPG) which performed a front-step exercise using a conical pulley, 2–3 sets of 6 repetitions each leg, during 9 weeks (CPG, n=10) in addition to its usual strength training, or to a control group (CG, n=10). The improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 25 publications
2
40
0
7
Order By: Relevance
“…Substantial improvements were found in ConMean (ES: 1.16 to 2.24), which is comparable with the range reported in previous studies (ES: 0.85 to 0.91) [25,28]. Regarding ConPeak power, other research studies [27] showed lower training effects (ES: 0.38 to 0.84) in comparison to the current study (ES: 0.77 to 1.63).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Substantial improvements were found in ConMean (ES: 1.16 to 2.24), which is comparable with the range reported in previous studies (ES: 0.85 to 0.91) [25,28]. Regarding ConPeak power, other research studies [27] showed lower training effects (ES: 0.38 to 0.84) in comparison to the current study (ES: 0.77 to 1.63).…”
Section: Discussionsupporting
confidence: 89%
“…Mostly, the effects of such training programs have been analyzed on specific physical abilities, such as jumping, sprinting, or changing direction [15,[20][21][22][23][24]. Nevertheless, even though mean and peak power have been examined, information concerning the influence of EOT on these variables is scarce [25][26][27][28]. Naturally, as they perform one task over time, one would expect them to improve with practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La parte experimental se ha desarrollado en las instalaciones de la Universidad Pontificia de Salamanca, los test fueron medidos por el mismo evaluador tanto al inicio como al final de la investigación, además fue formado este evaluador en la toma de datos para evitar errores. Los participantes pudieron practicar una semana antes la realización de los test en el laboratorio un total de dos intentos en cada uno, con un doble objetivo, familiarizarse con los test para evitar errores en la toma de datos y a su vez preparar al evaluador, similar a otro estudio (Núñez et al, 2019).…”
Section: Instrumentosunclassified
“…Sin embargo, existe otro método de entrenamiento que permitiría mejorar notablemente la fuerza excéntrica en los deportistas, eso sí utilizan la tecnología isoinercial la cual, va a permitir adaptaciones musculares fuertes y tempranas, en mayor medida que el entrenamiento con pesas tradicionales (Cabanillas et Los entrenamientos realizados mediante dispositivos inerciales utilizan la resistencia de inercia rotacional ofreciendo resistencia independiente de la gravedad, utilizando volantes giratorios durante el movimiento para generar la fuerza de inercia, con mayor carga excéntrica, que permite realizar movimientos en las tres dimensiones del espacio, adaptados individualmente y difiere de entrenamientos tradicionales, que utilizan principalmente el peso libre (Cabanillas et . Estos dispositivos están formados por un volante de rotación inercial, además de un eje que está fijo sobre el que giran las masas o pesos que pueden variar hasta un total de 16 pesos y, además, modifica la velocidad (Núñez et al, 2019). En un primer movimiento ocurre la fase concéntrica cuando la cuerda se desenrolla totalmente y cuando se recoge se trabaja la fase excéntrica (Vázquez-Guerrero & Moras, 2015), en este caso no hay fuerza de fricción lo que permite que ambas fuerzas sean iguales, permitiendo un gran esfuerza excéntrico y sin embargo con menor costo metabólico (Fiorilli et al, 2020).…”
Section: Introductionunclassified